Analytical Model for Optical Scattering of Infrared Laser by Nonspherical Raindrops - Jing Guo; He Zhang; Xiang-jin Zhang (International Journal of Optics)
Analytic model was developed to investigate the interaction of infrared laser with nonspherical raindrops. The method based on Fraunhofer diffraction and geometrical optics was presented to obtain the analytic solution for single-scattering properties by approximate ellipsoid raindrops. Light scattering patterns were obtained for different drop sizes and shapes. Computational results demonstrate that the scattering of raindrops was contributed by both Fraunhofer diffraction and geometric scattering, and the results obtained from analytic formulas were consistent with the conclusions of using Monte Carlo ray tracing approach.